Penerapan Kualitas Bahan Baku Kayu Pada Usaha Meubel Warsito Desa Jayakarta, Bengkulu Tengah - suryani, reni; Hidayah, Nenden Restu; Susena, Karona Cahya (Universitas Dehasen Bengkulu, 2023)
Warsito Furniture Business in Jayakarta Village, Bengkulu Tengah is one of the MSME industries. Starting from himself, Mr. Warsito made a furniture business called Warsito Furniture Business. This business was founded in 1998 with makeshift equipment. With high interest, this business began to develop and was eyed by the Social Welfare Service of Bengkulu Province. The Independent Family Joint Business Group (KUBE)